The Effectiveness of the Symbol in Iraqi Monodrama Texts: محمد علي ابراهيم (Al-Academy, 2019)
This research studies the effectiveness of the symbol in the Iraqi monodrama texts. The methodological framework is devoted to the research problem and the need for conducting it, its importance, the purpose of research, and the definition of the most important terms. The research problem dealt with the concept of the effectiveness of the symbol, the monodrama, and the working levels of the symbol in the monodrama texts of the author, in addition to the disclosure of the artistic vision embodied by the playwright in the use of the symbol within the literary product, as well as the development of the creative process. The research problem was defined by the following question: How effective is the symbol in the Iraqi Monodrama texts?The purpose of the research is: the effectiveness of the symbol in the Iraqi monodrama texts. This chapter consisted of the limits of the research, and the identification of the most prominent terms, while the theoretical framework included three sections: in the first one, the researcher addresses the symbol concept and effectiveness and clarified the most important terms adjacent to the symbol in terms of working convergence, while the second section was devoted to studying the effectiveness of the symbol by the language scientists. As for the third section, it was devoted to studying the effectiveness of the monodramatic symbol through tracking the concept of monodrama and the theoretical framework indicators.The researcher chose the play (Oil Spot) as a sample for the study. The most important results reached at were: the monodramatic texts of the writer Mahmoud Abu Al-Abbas were characterized by the dramatic and artistic perfection and the symbols are inspired by the character's social and psychological material and utilizing them according to the situation in the current age. The research ended with the conclusions and a list of sources and references.